Evaluating the Safety and the Effect of Blast Loading on the Shotcrete together with lattice girder Support of Tunnels (Fracture and Structural Integrity, 2023)
Damage to tunnels caused by explosions may damage the support structure and the stability. This damage is due to either blasting the working face for drilling progress or an explosion inside the tunnel. The present study investigates the dynamic parameters resulting from the blasting pattern on the temporary support structure of the tunnel considered as a lattice girder and shotcrete equivalent cross-section. For this purpose, LS-DYNA finite element software was used to assess the dynamic response of the structure to the vibration of the blasting-induced explosion. The peak particle velocity (PPV) was considered to evaluate the safety of the tunnel under dynamic loads. According to the results of this study, by exceeding the velocity of 0.9 m/s in the elements, some levels of destruction will occur. Regarding the elements of the temporary support structure of the tunnel, it is found that the damage occurs near the face and 2 m from the tunnel.
Keywords: tunnel lining; numerical modeling; blasting